Unveiling The Challenge of Student Scientific Writing: A Need Analysis - Yelliza Yelliza (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
This study addresses the pressing need for customized instructional materials aimed at improving students' competence in writing scientific articles. Despite the crucial role of this skill in academia, there is a noticeable scarcity of dedicated teaching resources, especially for research article writing. By investigating specific shortcomings faced by students and aligning them with tailored instructional strategies, this research aims to enhance students' academic writing abilities. Using a case study design, this research involved 72 students from the English Education Study Program at Universitas PGRI West Sumatera. Data collection utilized questionnaires adapted from existing literature, focusing on students' perceived shortcomings in writing scientific articles. Through this method, specific challenges encountered by students in the writing process were identified and analyzed. The analysis revealed that students' lack of writing scientific articles format research articles is in the high category, with an average of 4.28 (85.53%). From the data, nine statements are in the very high category, and 13 are in the high category. The statements in the very high category were ‘creating research gap’ (M=4.54), ‘Describing the data collection procedure’ (M=4.50), ‘Describing data analysis procedures’ (M=4.33), 'presenting meta-textual information’ (M=4.38), ‘presenting results’ (M=4.50), ‘providing background information (M=3.58), ‘Commenting on results or findings‘ (M=4.50),‘Restating the research objectives and approach‘ (M=4.63) and ‘evaluating research contributions’ (M=4.33). These findings underscore the importance of tailored instructional approaches to enhance students' scientific writing skills, ultimately improving the quality of education in preparing students for future academic endeavors.